Unfolded protein response in balancing plant growth and stress tolerance - Liu, Yao; Lv, Yonglun; Wei, An; Guo, Mujin; Li, Yanjie; Wang, Jiaojiao; Wang, Xinhua; Bao, Yan (Frontiers in Plant Science, 2022)
The ER (endoplasmic reticulum) is the largest membrane-bound multifunctional organelle in eukaryotic cells, serving particularly important in protein synthesis, modification, folding and transport. UPR (unfolded protein response) is one of the systematized strategies that eukaryotic cells employ for responding to ER stress, a condition represents the processing capability of ER is overwhelmed and stressed. UPR is usually triggered when the protein folding capacity of ER is overloaded, and indeed, mounting studies were focused on the stress responding side of UPR. In plants, beyond stress response, accumulated evidences have suggested that UPR is essential for growth and development, and more importantly, the necessity of UPR in this regard requires its endogenous basal activation even without stress. Then plants must have to fine tune the activation level of UPR pathway for balancing growth and stress response. In this review, we summarized the recent progresses in plant UPR, centering on its role in controlling plant reproduction and root growth, and lay out some outstanding questions to be addressed in the future.